Pengembangan Media Materi Keadaan Alam Di Indonesia Menggunakan Perangkat Lunak Videoscribe Pada Mata Pelajaran Ips Kelas Vii - Taufiq, Fillyas Rahmat, Drs.Suharjo,M.S (2016)
This research aims to (1) Develop learning media Social Studies class VII matter natural conditions in Indonesia using software VideoScribe. (2) determine the feasibility of learning media Social Studies class VII matter natural conditions in Indonesia software based VideoScribe. This research and development (R&D) using Sugiyono development model. Data collection techniques in the development of media video namely interview by asking questions to the teachers that are related with the needs of the learning media and techniques questioner done with how to give the question to the teacher of the students to know the needs of the media video expected. The techniques used after acquiring data using descriptive analysis techniques quantitative, namely with menganilisis from questionnaires obtained from questionnaires the needs of learning media. This research is carried out in the SMP N 2 Boyolali to test research products. Product development learning media using software VideoScrbe produce learning video with video title "Mengenali Keadaan Alam Indonesia". Learning video in the development of these worthy used because it has been through the validation and approval from the experts in the media. The results ekpserimen learning media used effectively in the learning process. Improvements on the results of student learning increased by 5 percent before the use of learning media. Key Words : Learning Media, Videoscribe, Development, Natural condition